Manajemen Modal Usaha Pada Usaha Mikro Di Desa Piloliyanga Kecamatan Tilamuta Kabupaten Boalemo - Sukrianto, Sukrianto (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2024)
Micro businesses are very good businesses whether owned by a person or an individual business entity. Most micro businesses in Piloliyanga Village do not have problems such as difficulty in getting additional capital to manage the business. So the aim of the research is to determine business capital management in Micro Enterprises in Piloliyanga Village, Tilamuta District, Boalemo Regency. Qualitative research method, the data sources used are primary and secondary data. The data collection methods used were observation, interviews and documentation. The data analysis methods used are three interactive models, namely data reduction, data presentation and conclusion drawing. The results of the research and discussion show that micro business capital management in Piloliyanga Village has positive impacts such as affordable prices which are more attractive to consumers so that the products and goods sold are of good quality, open employment opportunities which facilitate business growth so that there is potential for skill development and the use of social media as social media. Impacts such as negative promotion are very limited, causing micro business owners to only use free social media. Through better innovation or according to standards in supporting financial management, including planning, management and evaluation. Competitors are one of the biggest threats, giving the impression that consumers will compare. Limited product variations sometimes mean that consumers start to think and look for similar stores that are more complete.